The Study of English Teachers’ pre-service experience at Remote School Contexts - Isma Sari Ulang; Zakaria; Rais Abin; Roslina; Hariadi Syam; Muthmainnah Bahri A. Bohang (Universitas Islam Negeri Palopo, 2026)
Teaching English in remote schools presents unique challenges for pre-service English teachers due to limited educational facilities, restricted technological access, diverse student characteristics, and varying levels of student motivation. These contextual conditions require prospective teachers to adapt their instructional practices while maintaining meaningful student engagement throughout the learning process. This study aims to explore the experiences of pre-service English teachers during their teaching practicum in remote schools, focusing on the challenges they encountered, the instructional adaptation strategies they employed, the ways they promoted student engagement, and the professional growth that emerged from these experiences. A qualitative descriptive design was employed involving five pre-service English teachers from the English Education Study Program at Universitas Sembilan Belas November Kolaka who had completed their teaching practicum in remote schools. Participants were selected using purposive sampling. Data were collected through semi-structured interviews consisting of ten guiding questions and supported by practicum records and reflective documents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings revealed four major themes: (1) challenges in remote school teaching, including limited facilities, inadequate instructional media, technological constraints, and low student motivation; (2) instructional adaptation strategies through contextual teaching, collaborative learning, and flexible instructional practices; (3) promoting student engagement by employing game-based learning, positive classroom environments, interactive activities, and contextual learning experiences; and (4) professional growth and reflective practice developed through authentic teaching experiences. The study concludes that teaching practicum in remote schools serves as a transformative learning experience that enhances pedagogical competence, instructional adaptability, reflective practice, and professional readiness among pre-service English teachers. The findings provide practical implications for teacher education programs in preparing prospective English teachers for diverse educational contexts.